Mudanças fonológicas em sujeitos com desvio fonológico submetidos ao modelo de oposições máximas modificado utilizando contraste e reforço do traço [voz] - Silva, Ana Paula Silva da (2007)
This research aimed to analyze the phonological changes occurred in systems of subjects with phonological disorders submitted to phonological therapy through the Modified Maximal Opposition model using contrast and reinforcement of [voice] feature. Four people were part of this research, two male and two female subjects, with ages between 5:2 and 7:3 in the beginning of the study; 25 therapeutic sessions were done through the Modified Maximal Opposition model (Bagetti, Mota and Keske-Soares, 2005). The subjects were divided into two groups, one group treated with contrast , and the other with reinforcement . They found the generalization out each five sessions. As results, we observed that all the subjects presented changes in their phonological systems. The group treated with contrast presented superior performance in the generalization to items not used in the treatment and to other position in the word. The group treated with reinforcement presented superior performance related to the number of acquired segments, generalization into a sound class, and for other sound classes. So, we concluded that both groups presented phonological changes in their systems, some kinds of generalizations were bigger for the group treated with contrast , and others for the group treated with reinforcement .